Impulse magnetic stimulation facilitates synaptic regeneration in rats following sciatic nerve injury☆ - Zhivolupov, Sergey A. (Neural Regen Res, 2012)
The current studies describing magnetic stimulation for treatment of nervous system diseases mainly focus on transcranial magnetic stimulation and rarely focus on spinal cord magnetic stimulation. Spinal cord magnetic stimulation has been confirmed to promote neural plasticity after injuries of spinal cord, brain and peripheral nerve. To evaluate the effects of impulse magnetic stimulation of the spinal cord on peripheral nerve regneration, we compressed a 3 mm segment located in the middle third of the hip using a sterilized artery forceps to induce ischemia. Then, all animals underwent impulse magnetic stimulation of the lumbar portion of spinal crod and spinal nerve roots daily for 1 month. Electron microscopy results showed that in and below the injuryed segment, the inflammation and demyelination of neural tissue were alleviated, apoptotic cells were reduced, and injured Schwann cells and myelin fibers were repaired. These findings suggest that high-frequency impulse magnetic stimulation of spinal cord and corresponding spinal nerve roots promotes synaptic regeneration following sciatic nerve injury.